‘SAME SAME, BUT DIFFERENT’: AN INQUIRY INTO PARADISE IMAGERY OF TOURISM INDUSTRY AND TOURIST PRACTICES (ЕтноАнтропоЗум/EthnoAnthropoZoom, 2011)
Image of the ‘paradise’ is a conventional icon of mass tourism industry and is most often represented as a solitary tropical island with palm trees, beaches and the like. However, this symbol has been represented in many other contexts, not only in advertising of island tourism. As such, it has developed into a world-wide symbol, to which different emphasis and meanings have been attached, depending on types and goals of individual cultural production or meaning. With different implications of ‘the paradise’ in mind, I will try to systematize its actualizations and rethink its power and value in contemporary tourist practices of Western backpackers and travellers in postcolonial worlds
Keywords: paradise image; tourism; post colony; tropics; island